2018
DOI: 10.1016/j.actamat.2017.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Saturation of tungsten surfaces with hydrogen: A density functional theory study complemented by low energy ion scattering and direct recoil spectroscopy data

Abstract: Herein, we investigate the saturation limits of hydrogen on the (110) and (100) surfaces of tungsten via Density Functional Theory (DFT) and complement our findings with experimental measurements. We present a detailed study of the various stable configurations that hydrogen can adopt upon the surfaces at coverage ratios starting below 1.0, up to the point of their experimental coverage ratios, and beyond. Our findings allow us to estimate that the saturation limit on each surface exists with one monolayer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 51 publications
3
49
1
Order By: Relevance
“…This is in good agreement from past results reported by Hodille et al [13] but still lower than the results reported by Frauenfelder. This can be explained by the fact that Frauenfelder conducted his experiment at a much higher temperature of about a 1000 K where the surface D coverage was much lower than in our case where the experiment was done at 600 K. Some DFT calculations [36] and also our own experimental results [37] indicate that the chemisorption energy of the surface depends on the D coverage, increasing with falling coverage. From our recent results [37] we see that indeed at higher exposure temperatures E ef f bulk + E ch = 1.9 eV which is much closer to the value reported by Frauenfelder.…”
Section: Simulationmentioning
confidence: 58%
“…This is in good agreement from past results reported by Hodille et al [13] but still lower than the results reported by Frauenfelder. This can be explained by the fact that Frauenfelder conducted his experiment at a much higher temperature of about a 1000 K where the surface D coverage was much lower than in our case where the experiment was done at 600 K. Some DFT calculations [36] and also our own experimental results [37] indicate that the chemisorption energy of the surface depends on the D coverage, increasing with falling coverage. From our recent results [37] we see that indeed at higher exposure temperatures E ef f bulk + E ch = 1.9 eV which is much closer to the value reported by Frauenfelder.…”
Section: Simulationmentioning
confidence: 58%
“…From the experimental point of view, much effort has been put on Thermal Desorption Spectroscopy (TDS), also called Temperature Programmed Desorption (TPD) [12][13][14][15], and on ion beam analysis, such as Nuclear Reaction Analysis (NRA) [16][17][18][19] or Second Ions Mass Spectrometry (SIMS) [20]. Elastic Recoil Detection Analysis (ERDA) [21], Low Energy Ion Scattering (LEIS) and Direct Recoil Spectroscopy (DRS) [22][23][24] are also used, mostly to gain information on the surface properties. TDS can access global information related to the binding state of hydrogen in the bulk and on the surface, while ion beam analysis accesses local From the theoretical point of view, calculations and simulations have been carried out from the atomistic scales using Density Functional Theory (DFT) [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and Molecular Dynamics (MD) [39][40][41][42][43], to the macroscopic scale using Kinetic Monte Carlo (KMC) [44][45][46][47] and Macroscopic Rate Equations (MRE) [15,[48][49][50]…”
Section: Introductionmentioning
confidence: 99%
“…Experimental [3,4,13,14] and theoretical evidence [1] suggests that at room temperature, and low pressure conditions, the W(110) surface saturates at a mono-layer of hydrogen, corresponding to a coverage ratio of Θ = 1.0. In all published DFT works, the so-called "three-fold" (TF) site is found to be the most stable [1,22] for a single hydrogen adsorbing on the surface. LEED studies suggest that from below 30 K to beyond 400 K various well-ordered patterns emerge [3,4,13,14].…”
Section: 1astable Adsorption Patternsmentioning
confidence: 99%
“…For a more detailed analysis of the stationary configurations that hydrogen can form up to and beyond Θ = 1.0, the interested reader is referred to our previous work [1]. Considering coverage Θ ≥ 0.75, the local electronic potential near a TF site is effectively different than that of a less-saturated surface as is seen by the increase in .,Θ corresponding to a loss in stability per hydrogen atom at 0 K. The same trend continues at Θ = 1.0 where there is a full mono-layer of hydrogen and the saturation coverage has been reached according to single crystalline LEED [3,4], LIES [1], and TDS experiments [2].…”
Section: 1astable Adsorption Patternsmentioning
confidence: 99%
See 1 more Smart Citation